The influence of imposed strain rate on fracture of surface oxides. - Hancock, P.; Nicholls, John R.; Mahmood, K. (Elsevier Science B.V., Amsterdam., 1993)
The mechanical properties of chromium rich scales formed on 304 stainless steel have been investigated as a function of deformation rate and operating temperature. At 900C at slow strain rates < 10-6 per second no cracking was observed at strains up to 10%. At rapid strain rates in excess of 10-4 per second oxide cracking was found to be independent of strain rate and controlled by the fracture toughness of the oxide. In the intermediate region, with strain rates between 10-4 per second and 10-6 in the temperature range 700 to 950C, the behaviour is determined by the creep deformation and fracture mode of the oxide. The mechanism of surface oxide failure is examined and an equation to predict cracking density over the full range of both monotonic tensile and creep fracture modes is sugg